Efeitos da facilitação por espécies nativas na restauração da Mata Atlântica - Cristiani Spadeto (2019)
In this thesis I evaluated the facilitating role of some arboreal tree species (facilitating species) of the Atlantic Forest and how these species influence the planted seedlings and the natural regeneration of environments in the process of forest restoration. The thesis is divided into two chapters. Chapter I presents how the facilitating species (Senna macranthera (DC. Ex Collad.) H.S. Irwin & Barneby and Croton floribundus Spreng) improve the environment under their canopy and how they influence seed germination, survival and growth of planted seedlings. Chapter II evaluates the phylogenetic and functional structure, and taxonomic, functional and phylogenetic diversity of natural regeneration. Paired comparisons of the β diversity were made for all facets of the diversity that regenerated under the species: Bixa arborea Huber, Inga laurina (Sw.) Willd., Joannesia princeps Vell. and Senna multijuga var. verrucosa (Vogel) H.S. Irwin & R.C. Barneby. The allelopathic effect of leaves of these species was evaluated through the seed germination test. The results of these studies indicate that the facilitating species reduce light intensity under their canopy when compared to open areas and improve seed germination and seedling growth, suggesting that the age of facilitated species is an important modulator of facilitation interactions. The facilitating species do not modulate the phylogenetic structure of natural regeneration, but they influence the phylogenetic and functional diversity in the regenerating community under their canopies, as some species may have an allelopathic effect. These results may add to the existing knowledge about forest restoration and assist decision making in relation to the set of species to be implanted in future restoration projects.